The Mesopelagic Scattering Layer: A Hotspot for Heterotrophic Prokaryotes in the Red Sea Twilight Zone - Calleja, Maria L.; Ansari, Mohd I.; Røstad, Anders; Silva, Luis; Kaartvedt, Stein; Irigoien, Xabier; Morán, Xosé Anxelu G. (Frontiers in Marine Science, 2018)
The vast majority of marine dissolved organic carbon (DOC), the largest reservoir of reduced carbon on Earth, is believed to accumulate in the abyssal layers of the ocean over timescales of decades to millennia. However, evidence is growing that small animals that migrate vertically every day from the surface to mesopelagic layers are significantly contributing to the active vertical flux of organic matter. Whether that represents an important source of carbon available for microbial production and respiration at the mesopelagic realm, and its contribution to oceanic carbon budgets and energy flows, is yet to be explored. Here we present data suggesting that Red Sea migrating animals may produce an overlooked source of labile DOC (used at a mean rate of 2.1 µmol C L-1 d-1) that does not accumulate but fuels the metabolism of prokaryotic heterotrophs in the twilight zone, generating a disregarded hotspot for heterotrophic prokaryotes.